2020
DOI: 10.15446/revfacmed.v68n4.76519
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health and safety in agriculture. A systematic review

Abstract: Este artículo fue aprobado para publicación en el v68n4 de la Revista de la Facultad de Medicina teniendo en cuenta los conceptos de los pares evaluadores y los cambios realizados por los autores según estos conceptos. Por lo tanto, se publica la versión preliminar del artículo para su consulta y citación provisional, pero debe aclararse que esta puede diferir del documento final, ya que no ha completado las etapas finales del proceso editorial (corrección de estilo, traducción y diagramación) y solo los títul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 86 publications
0
8
0
2
Order By: Relevance
“…Reasons for facing health and safety risks were identi ed as alternatives. These are Awareness and lack of information, education/literacy level, transportation, insu cient vocational information, inadequate accommodation, and working conditions; age, gender and child employee; the use of appropriate personal protective equipment ( [46]; [41]; [47]; [48]; [20]). Alternatives are shown in Figure 5.…”
Section: Identifying Alternativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Reasons for facing health and safety risks were identi ed as alternatives. These are Awareness and lack of information, education/literacy level, transportation, insu cient vocational information, inadequate accommodation, and working conditions; age, gender and child employee; the use of appropriate personal protective equipment ( [46]; [41]; [47]; [48]; [20]). Alternatives are shown in Figure 5.…”
Section: Identifying Alternativesmentioning
confidence: 99%
“…They analyzed approaches to minimizing the occurrence of injuries together with safe cooperation methods to overcome these hazards. Molina-Guzmán and Ríos-Osorio [20] reviewed the current literature's occupational health and risks in agriculture. Chauhan et al [21] have done their work to investigate ergonomic risks and achieve more e cient manual tasks while performing picking tasks in agricultural sectors in India.…”
Section: Introductionmentioning
confidence: 99%
“…Estudios internacionales muestran que las condiciones de vida y trabajo precarias de las personas migrantes que trabajan en agricultura tienen consecuencias directas en su salud y calidad de vida (11)(12)(13) . Por una parte, el acceso a una vivienda digna y otros recursos básicos como la alimentación, dependen de la percepción de ingresos.…”
Section: Impacto En La Saludunclassified
“…Por último, las personas migrantes, especialmente aquellas en situación administrativa irregular, se enfrentan a barreras de acceso a los servicios sanitarios (6,(11)(12)21) que han sido agravadas durante la actual crisis sanitaria derivada de la pandemia del Covid19. Se sabe que, durante las crisis económicas, el deterioro de las condiciones de trabajo y empleo en los sectores más inestables como la agricultura, coloca a los trabajadores migrantes no calificados en una situación de gran inestabilidad produciendo efectos negativos en su salud (22) .…”
Section: Editorial Editorialunclassified
“…The case-control study in agriculturists of Khon Kaen found that noise-induced hearing loss was 49.7%. 27 Work-related injuries had a prevalence of 20.1% among the farmers of the Phayao province 28 and the prevalence of heatrelated disease was also reported as 13.5 per 100,000 farmers, or 0.014%, in agriculturists of the Khon Kaen province. 29 Those work-related diseases and injuries in Thailand were identified by the International Statistical Classification of Diseases and Related Health Problems 10 th revision (ICD-10) 30 (https://icd.who.int/browse10/2019/en) and the specified Y96 external code (work related condition).…”
Section: Introductionmentioning
confidence: 99%